MOTIVATION AND INTEREST: DOES IT HAVE AN INFLUENCE ON PJOK LEARNING OUTCOMES IN ELEMENTARY SCHOOL CHILDREN? - Hasmirati Hasmirati; Nursyamsi SY; Mustapa Mustapa; Heri Dermawan; I Putu Agus Dharma Hita (Journal on Research and Review of Educational Innovation, 2023)
Learning outcomes have an important role in the learning process. This is because learning outcomes can be used as a benchmark to find out how far changes in students after receiving their learning experience can be observed and measured in the form of knowledge, attitudes, and skills. This study aims to determine whether there is an influence of motivation to learn and interest in learning on the learning outcomes of PJOK subjects. This study uses a type of correlational research with multiple regression techniques. This research was conducted at SDN 4 Dauhwaru with a total sample of 30 people consisting of 15 students and 15 female students. Data collection techniques for the level of motivation and interest in learning in this study used a questionnaire while the learning outcomes used skill scores in PJOK subjects. The results of this study are that motivation and interest in learning have a positive influence on learning outcomes in PJOK subjects.